ACTIVE CHARACTERISTICS OF SAM NUA FAULT ZONE DURING NEOTECTONIC STAGE - Thom, Bui Van; Hung, Nguyen Van; Sunlinthone, Oneta; Duangpaseuth, Somsanith; Vongxaiya, Soutthiphong; Markvilay, Bounpaphan (Vietnam Journal of Earth Sciences, 2014)
The Sam Nua fault zone lies in the Sop Cop fault zone (in the NW of Vietnam). In Laos, the Sam Nua fault zone composed of two fault branches, which are the main branch called Na Vine - Nam and Tham Pong - Na Ham fault. The first part of fault zone is NW-SE directed extension while the southeastern end turns gradually to latitude direction and sloping NW. In the present - day tectonic period, it has been undergone two stages of motion: right lateral slips in the Miocen - Pliocen time and left lateral slip in the latter phase (Pliocen - Quatylity). The amplitude of horizontal movement is estimated approximately 1200m at a slip - rate of 4mm/year and the vertical is 50m. Recently, this fault zone has been reactivated with a magnitude 5.5 Richter by earthquake recorded. This study will attribute to reveal the process of displacement in Sop Cop fault zone.ReferencesNguyễn Văn Hùng, 2002. Đặc điểm cơ bản đứt gãy hoạt động khu vực tây bắc. Luận án Tiến sỹ Địa chất. Lưu trữ tại Thư viện Quốc gia.Nguyễn Văn Hùng, Hoàng Quang Vinh, 2004. Về hoạt động của các đới đứt gãy Tân kiến tạo ở Tây Bắc Bộ Việt Nam. Tạp chí Địa chất, loạt A số 285, tr.38-48.Bùi Văn Thơm, 2002. Một số đặc điểm đứt gãy tân kiến tạo khu vực Bắc Trung Bộ. Luận án Tiến sỹ. Lưu trữ tại Thư viện Quốc gia.Nguyễn Đình Xuyên (chủ biên), 2003. Nghiên cứu động đất và dao động nền lãnh thổ Việt Nam. Báo cáo Đề tài cấp Nhà nước Viện Vật lý Địa cầu, Hà Nội.Nguyễn Trọng Yêm (chủ biên), 2005. Thiên 107 tai nứt đất lãnh thổ Việt Nam và các giải pháp phòng tránh giảm nhẹ thiệt hại. Đề án điều tra cơ bản. Viện Khoa học và Công nghệ Việt Nam.Daninovich DN, 1961. The method of the study of crack zones  associated with faults. Methodical rukovostvo, Irkursk.Nikolaev P. N., 1992. Methods of analysis tectono-dynamics  Science. Mockva.Semensky KK, 1991. A new aproach to study the tectonic fractures in discontinuous zones. Geology and Geophysics N0 5 , Novosibirsk.Sherman SI, Dneprovskiy YI, 1968. stress field of the Earth's crust and the geological - structural methods of study  Novosibirsk.